1989
DOI: 10.1042/bj2580101
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of a membrane-bound enzyme as a model for anaesthetic action and drug toxicity

Abstract: The inhibition of the membrane-bound enzyme cytochrome c oxidase by aliphatic n-alcohols and other neutral organic compounds was studied as a model for anaesthetic action and drug toxicity. The n-alcohols (C1 to C14) displayed a variation in inhibition constant of over 500,000-fold. The inhibition constants correlated well with the number of carbon atoms in the n-alcohols and also their n-octanol/water partition coefficients. General anaesthetic potency is known to be similarly well correlated with octanol/wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…This is exemplified by the fact that inborn errors of cardiolipin biosynthesis lead to diseases causing mitochondrial dysfunction (Barth syndrome) due to destabilization of the respiratory chain supercomplexes, specifically cytochrome c oxidase (55,56). Despite the lack of detailed information about the mechanism by which sphinganine, sphingosine, and C16-ceramide gain access to complex IV in mitochondria, our data are consistent with the idea that their mode of interaction is highly specific and may involve competition with either the cytochrome c binding site or displacement of phospholipids that are bound to the enzyme (57).…”
Section: Discussionsupporting
confidence: 77%
“…This is exemplified by the fact that inborn errors of cardiolipin biosynthesis lead to diseases causing mitochondrial dysfunction (Barth syndrome) due to destabilization of the respiratory chain supercomplexes, specifically cytochrome c oxidase (55,56). Despite the lack of detailed information about the mechanism by which sphinganine, sphingosine, and C16-ceramide gain access to complex IV in mitochondria, our data are consistent with the idea that their mode of interaction is highly specific and may involve competition with either the cytochrome c binding site or displacement of phospholipids that are bound to the enzyme (57).…”
Section: Discussionsupporting
confidence: 77%
“…The binding sites for volatile anesthetics on several synaptic receptor proteins appear to be associated with hydrophobic pockets (6)(7)(8) and, consistent with the relatively unspecific nature of hydrophobic interactions, these compounds also bind to proteins not primarily associated with nervous system function (9), including cytochrome c oxidase, adenylate kinase, and luciferase (5,10,11). The general nature of this hydrophobic binding mechanism raises the possibility that volatile anesthetics may have additional, as yet unrecognized, neuronal targets.…”
mentioning
confidence: 99%
“…The selected electron donor and acceptor of NBO interactions of the optimized complexes and their second-order delocalization energy DE (2) are collected in Table 7. It could be seen that the DE (2) of n (O14) ?…”
Section: Nbo Analysismentioning
confidence: 99%
“…In PÁC(O2;H1) and PÁC(N3;H4a), the total DE (2) contribution of O14 is 16.58 and 12.54 kcal/mol, respectively, suggesting the energy stabilization due to charge transfer in the former is stronger than the latter. The calculated total values for O14 involved DE (2) pertaining to the related bond lengths and length angles of all the complexes were investigated. The results showed that the energy stabilization due to the charge transfer appears to roughly correlate with the internuclear distance r(OÁÁÁH) and the relationship is shown in Fig.…”
Section: Nbo Analysismentioning
confidence: 99%
See 1 more Smart Citation